2019
DOI: 10.18203/2320-6012.ijrms20191670
|View full text |Cite
|
Sign up to set email alerts
|

Management of displaced transverse fractures of the patella using tension band wiring with or without circumferential cerclage wiring: A comparative study

Abstract: Background: Transverse fractures of body of the patella are by far the most common fractures of this bone. Surgical fixation is the recommended treatment in displaced fractures with extensor lag. Although, tension band wiring (TBW) technique is the gold standard for these fractures, few surgeons recommend augmentation with circumferential cerclage wiring to improve the strength of the fixation. We compared the results of the internal fixation of displaced transverse fractures of the patella using TBW and circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
2
1
0
Order By: Relevance
“…[17][18][19] Fractures were more common on the right side (59.1%), than on left side (40.9%) which were in agreement with previous studies Asimuddin et al and Mahindra et al 18,20 In the present study, 17 (%) were males and 5 (%) were females, with male to female (M: F) ratio of 3.4:1. Similar observations were made by Asimuddin et al, Ramu et al and Lone et al [20][21][22] In our study, the most common cause of fracture was road traffic accident (%), followed by fall (%), and assault which was similar to previous studies Asimuddin et al, Mohapatra et al and Mahindra et al 17,18,20 Table 3: Time of radiological union.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[17][18][19] Fractures were more common on the right side (59.1%), than on left side (40.9%) which were in agreement with previous studies Asimuddin et al and Mahindra et al 18,20 In the present study, 17 (%) were males and 5 (%) were females, with male to female (M: F) ratio of 3.4:1. Similar observations were made by Asimuddin et al, Ramu et al and Lone et al [20][21][22] In our study, the most common cause of fracture was road traffic accident (%), followed by fall (%), and assault which was similar to previous studies Asimuddin et al, Mohapatra et al and Mahindra et al 17,18,20 Table 3: Time of radiological union.…”
Section: Discussionsupporting
confidence: 92%
“…Our results were comparable with the existing literature Asimuddin et al, Mahindra et al and Lone et al 18,20,22 No neurovascular complications were observed in the present study.…”
Section: Studysupporting
confidence: 93%
See 1 more Smart Citation
“…4%) had a fair outcome. The findings of our study were consistent with those of Asimuddin et al, Mohapatra, and Lone et al[10,13,15]. Among the 50 patients, problems were found in 17 individuals, representing a prevalence rate of 34%.…”
supporting
confidence: 93%
“…Hardware complications were seen in six individuals, leading to the removal of the implant after the fracture had fully healed. [11,13,15]. The current investigation did not notice any neurovascular problems.…”
Section: Resultssupporting
confidence: 41%